Maternal complication of instrumental vaginal delivery and its associated factors: Systematic review and meta-analysis. - Hinsermu Bayu Abdi; Elias Bekele Wakwaya; Beyene Sisay Damtew; Beker Ahmed Hussen; Teresa Kisi Beyen (PLoS ONE)
Background While instrumental vaginal delivery is generally a safe procedure, but it is associated with significant risks for both the mother and the newborn in developing countries. However, burden of maternal instrumental delivery complications and its predictors in Ethiopia is highly varied and there isn't data that indicate nation-level cumulative evidence. Therefore, this study aimed to assess pooled prevalence of maternal complication related to instrumental vaginal delivery and its associated factors among mothers who underwent instrumental vaginal delivery in Ethiopia. Methods In this study, we conducted a search on PubMed, Scopus, Cochrane library, HINARI, and Google Scholar academic databases for studies published until August 2024. Keywords such as instrumental delivery, forceps, vacuum, complication, factors and Ethiopia were used to access literatures from the databases. For quality assessment and data extraction, The Joanna Briggs Critical Appraisal Tools and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were utilized. Random-effect model was used to calculate the pooled prevalence of maternal complication of instrumental vaginal delivery. Subgroup analyses were also conducted to explore potential heterogeneity. The publication bias was assessed using Funnel plot and Egger's. Results A total of 12 studies with 3745 study participants were participated in the present meta-analysis. The pooled prevalence of maternal complication of instrumental vaginal delivery was 21% (95% CI, 15.0%-28.0%). The prevalence of maternal complication was significantly different among studies conducted between ([2015-2020), and those conducted between [2020 and 2024]. Lowest (14%) in studies conducted before 2020 and highest (26%) among studies conducted 2020 and after (P-value<0.001). Type of instrument (AOR: 1.99, 95% CI: 1.37-2.90), episiotomy status (AOR: 3.49, 95% CI: 2.12-5.76), birthweight (AOR: 3.06, 95% CI: 1.88-4.97) and parity (AOR = 2.96, 95%CI: 1.80-4.85) were the factors associated with maternal complication of instrumental vaginal delivery. Conclusion Our study shows that approximately one in five mothers who underwent instrumental vaginal delivery develop serious maternal complication. Type of the instrument, episiotomy status, birthweight and parity were important predictors of the maternal complication of instrumental vaginal delivery. Effective evaluation of indication, contra indication and precondition for each instrument helps to prevent the maternal complication of instrumental vaginal delivery. Trial registration Registered in PROSPERO with ID: CRD42022366360.